THE OPHIOLITE-BEARING MÉLANGE IN THE EARLY TERTIARY PINDOS FLYSCH OF ETOLIA (CENTRAL GREECE) - Bortolotti, Valerio; Carras, Nicola; Chiari, Marco; Fazzuoli, Milvio; Marcucci, Marta; Nirta, Giuseppe; Principi, Gianfranco; Saccani, Emilio (Ofioliti, 2009)
In Etolia (Central Greece), west of the Parnassus/Vardoussia units, the Pindos succession crops out, with its higher formation: the Pindos Flysch. In its upper portion levels of debris flow deposits and slide blocks (olistostromes and olistoliths) contain ophiolitic material with fragments derived from the Parnassus/ Vardussia formations. This ophiolitic material consists of serpentinites, basalts of WPB, E- and N-MOR affinity, and radiolarian cherts of Middle-Late Triassic and Middle-Late Jurassic age. Petrologic and biostratigraphic analyses confirm that the mélange has the same features of the sub-ophiolitic mélanges present at the base of the ophiolitic masses in Greece. Linked to the flysch, with contacts of unclear nature, a rhyolites body of Middle Triassic age indicates the continental nature of the Pindos Basin. In fact, here, as all over the Albanian-Greek section of the Dinarides, no record of an oceanic area in the central portion of the Dinarides exists: the Parnassus and Vardoussia units were directly thrust onto the Pindos Basin. The intercalations of ophiolitic and continent-derived material in the flysch, are interpreted as the forerunners of the Ophiolitie Nappe which, coming from the Vardar Ocean located to the east, reached during the Eocene the Pindos Basin.